Laparoscopic colorectal surgery: learning curve and training implications. Issue 958 (5th August 2005) - Shah, P R; Joseph, A; Haray, P N
Abstract : Aims: This paper is a review of experience of laparoscopic colorectal surgery at a district general hospital with particular emphasis on the learning curve and training implications. Methods: All patients undergoing colorectal surgery where laparoscopy was attempted between March 1998 and October 2003 were included in this study. Results: There were 80 patients of which 49 had malignancy. Twenty eight stomas and 52 bowel resections were performed laparoscopically. The conversion rate for bowel resection was 32% (decreasing from 38% to 44% to 22%). This was significant (p = 0.001) when compared with stoma formation (7%). The firm has support from a specialist registrar and staff grade surgeon. In 22% of cases, one of the middle grades was the principal operating surgeon, mainly laparoscopic mobilisation and stoma formation. Only 6% of resections were performed by the middle grades. Conversely, a middle grade was the main operating surgeon in 66% of open resections and 61% of stoma formations during the same period. There were in all two deaths and 14 postoperative complications. All patients who had laparoscopic resections for malignancy had clear resection margins. Conclusion: This audit highlights that there is a long learning curve in laparoscopic colorectal surgery with decrease in conversion rates with increasing experience. There is also a reduction in training opportunities in open surgery during the learning phase of the consultant, although this may be counterbalanced by the exposure to laparoscopic techniques. Laparoscopic colonic mobilisation, as a part of stoma formation, is a good starting point for specialist registrar training.